Hubungan Asupan Kalsium dan Serat dengan Kejadian Kanker Kolorektal - , NINA ADLINA AFRAH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: The prevalence of colorectal cancer has been significantly increased within the last 20 years. Colorectal cancer is a malignant disease with high mortality rate. Along with a life style change into sedentary ones, this case is likely often found in our society. Low intake of calcium and fiber are some of these risk factors in colorectal cancer. Objective: This study aimed to determine the association between calcium intake and dietary fiber with colorectal cancer Method: This is an observational study using case-control design with matching on gender. This study was conducted in August 2013 - December 2013 in Dr. Sardjito Hospital Yogyakarta. The subject of this study was men or women aged above 18 years old who are patients hospitalized at RSUP Dr. Sardjito. We took 78 respondents that consist of 39 respondents as a control group and 39 respondents as a case group with a consecutive sampling method to complete the semiquantitative food frequency questionnaire to evaluate dietary calcium and fiber intake. Results: The average of daily calcium intake in case group was 420.697Â±30.9923 mg and in control group was 463.897Â± 46.7321 mg. There was no significant association betweencalcium intake and colorectal cancer (p=0.282